Simulation and experimental research of Langmuir probe operation in electro-negative plasma - Dudin, S.V.; Rafalskyi, D.V.; Naymark, D.A. (Вопросы атомной науки и техники, 2012)
The mathematical model of single cylindrical Langmuir probe describing dependence of positive ion current gathered by the probe on the basic parameters of electronegative plasma, such as probe potential, densities of electrons, positive and negative ions, relation between ion and electron temperatures is built. The model is based on the theory of the radial motion of charged particles. The model covers wide parameters domain of the electronegative plasma, particularly the whole range typical for technological systems. The experimental measurements, confirming the high reliability of the model are reported. The model can be used in probe measurements of electronegative plasma parameters in laboratory and technological systems, as well as for further theories perfection of surface layers in gas-discharge plasma.